2021
DOI: 10.3390/biomedicines9070750
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Bone Marrow-Derived Mesenchymal Stem Cells Following Chemotherapy

Abstract: Cisplatin (CP) is extensively used in the medical oncology field for malignancy treatment, but its use is associated with neurological side effects that compromise the patients’ quality of life. Cytotherapy is a new treatment strategy for tissue damage that has recently emerged. The use of bone marrow-derived mesenchymal stem cells (BM-MSCs) was investigated for its therapeutic potential against CP-induced chemobrain as well as various models of brain damage. This study was carried out to elucidate, for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…Treatment with HP L. and HP.NE promoted proliferation in the brain tissue after Cis administration via significant improvement in the Ki-67 marker. These results were consistent with previous studies that demonstrated the anti-inflammatory and preservative action of HP L. [ 16 , 61 ]. Based on the previously mentioned results, utilizing antioxidant, anti-inflammatory, and anti-apoptotic agents such as HP L. and HP.NE to guard against Cis-induced cerebral apoptosis is a logical strategy.…”
Section: Discussionsupporting
confidence: 94%
“…Treatment with HP L. and HP.NE promoted proliferation in the brain tissue after Cis administration via significant improvement in the Ki-67 marker. These results were consistent with previous studies that demonstrated the anti-inflammatory and preservative action of HP L. [ 16 , 61 ]. Based on the previously mentioned results, utilizing antioxidant, anti-inflammatory, and anti-apoptotic agents such as HP L. and HP.NE to guard against Cis-induced cerebral apoptosis is a logical strategy.…”
Section: Discussionsupporting
confidence: 94%
“…Nguyen and Ehrlich described multiple other drugs that could potentially be repurposed for treating CRCI (160). Preclinical studies have evaluated several novel agents including PAN-811, a ribonucleotide reductase inhibitor (161), mesenchymal stem cells (162)(163)(164), functionalized mitochondria (165), dual leucine zipper kinase (166), histone deacetylase 6 inhibitor (167), KU-32, for mitochondrial repair (168), and astaxanthin, an antioxidant (169), among others. However, these treatments have yet to be translated into clinical studies.…”
Section: Interventions For Crcimentioning
confidence: 99%